1α, 25‐dihydroxyvitamin D3 in combination with transforming growth factor‐β increases the frequency of Foxp3+ regulatory T cells through preferential expansion and usage of interleukin‐2. Issue 1 (September 2014) - Chambers, Emma S.; Suwannasaen, Duangchan; Mann, Elizabeth H.; Urry, Zoe; Richards, David F.; Lertmemongkolchai, Ganjana; Hawrylowicz, Catherine M.
Summary A high prevalence of vitamin D insufficiency and deficiency exists worldwide, which is associated with an increased incidence and severity of a range of immune‐mediated diseases. This has resulted in considerable interest in the immunodulatory functions of vitamin D. The active form of vitamin D, 1α, 25‐dihydroxyvitamin D3 [1, 25(OH)2D3], has been shown to increase the frequency of Foxp3+ CD4+ T regulatory (Treg) cells when present at high concentrations or under strong T‐cell stimulation in culture. Supporting evidence exists in vivo for a positive association between serum 25(OH)D and Foxp3+ Treg cell numbers in humans. The aim of this work was to identify the cytokine milieu required in vitro to promote Foxp3+ Treg cells in cultures containing 1, 25(OH)2D3 at more moderate concentrations (10−7 m). Stimulation of human CD4+ T cells with a combination of 1, 25(OH)2D3 and transforming growth factor‐β (TGF‐β) greatly increased the frequency of Foxp3+ Treg cells, which is proposed to result from the preferential expansion of Foxp3+ Treg cells, as compared with the Foxp3− effector T cells, in culture. The differential effect on proliferation may result from enhanced availability and usage of interleukin‐2 by the Foxp3+ Treg cells compared with Foxp3− effector T cells. In summary, modulation of the cytokine environment to one high in TGF‐β in the presence of 1, 25(OH)2D3 (10−7 m) significantly increased Foxp3+ Treg cell frequency. These data provide additional evidence for the important immunomodulatory properties of 1, 25(OH)2D3 that exist and may help to control inflammatory diseases.